Pengaruh Brand Image Dan Harga Tiket Terhadap Keputusan Berkunjung Ke Wisata Pulau Mandeh Kabupaten Pesisir Selatan - Irfan Irfan; Sophan Sophian (Pusat Riset dan Inovasi Nasional, 2023)
The research was conducted on Mandeh Island tourism in Pesisir Selatan Regency. The aim is to analyze the influence of brand image and ticket prices on the decision to visit Mandeh Island tourism in Pesisir Selatan Regency. This study uses quantitative methods. The population is tourists who visit Mandeh Island tourism as many as 100 respondents. The sampling technique is accidental sampling, so the sample in this study is 100 respondents. Data analysis used multiple linear regression analysis assisted by the computer program SPSS For Windows version 21. The results showed that brand image partially had a positive and significant effect on the decision to visit Mandeh Island tourism in the southern coastal district, ticket prices partially had a positive and significant effect on the decision Visiting Mandeh Island, South Coastal District.